2009
DOI: 10.1016/j.rse.2008.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral remote-sensing algorithms for particulate organic carbon (POC): The Gulf of Mexico

Abstract: To greatly increase the spatial and temporal resolution for studying carbon dynamics in the marine environment, we have developed remote sensing algorithms for particulate organic carbon (POC) by matching in-situ POC measurements in the Gulf of Mexico with matching SeaWiFS remote sensing reflectance. Data on total particulate matter (PM) as well as POC collected during nine cruises in spring, summer and early winter from 1997-2000 as part of the Northeastern Gulf of Mexico (NEGOM) study were used to test algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 51 publications
0
54
0
1
Order By: Relevance
“…Correlation-based algorithms are used to map chlorophyll (O'Reilly et al, 1998), POC (Son et al, 2009;Stramski et al, 1999Stramski et al, , 2008, PM (Vantrepotte et al, 2011), PIC (Balch et al, 2007), and phytoplankton functional groups (Alvain et al, 2005;IOCCG, 2014). They tend to work best in open ocean conditions where the assumptions that phytoplankton and associated constituents co-vary and primarily modulate ocean color are valid.…”
Section: Remotely-sensed Ocean Colormentioning
confidence: 99%
“…Correlation-based algorithms are used to map chlorophyll (O'Reilly et al, 1998), POC (Son et al, 2009;Stramski et al, 1999Stramski et al, , 2008, PM (Vantrepotte et al, 2011), PIC (Balch et al, 2007), and phytoplankton functional groups (Alvain et al, 2005;IOCCG, 2014). They tend to work best in open ocean conditions where the assumptions that phytoplankton and associated constituents co-vary and primarily modulate ocean color are valid.…”
Section: Remotely-sensed Ocean Colormentioning
confidence: 99%
“…Although POC generally represents only around 4-5 × 10 9 t C of total carbon in marine surface waters, it plays an important role in the global carbon cycle [2]. POC is important in regards to its role in sequestering carbon, scavenging associated elements and compounds, and sinking to the bottom as part of "the biological pump" [1][2][3]. Moreover, compared with POC stock in the ocean surface, the flux from DIC to POC has been estimated at about 50 × 10 9 t C·yr −1 [2].…”
Section: Introductionmentioning
confidence: 99%
“…Suspended particles can scatter light back to space, with backscattered light being able to be received by remote sensing sensors. Some researchers have reported on relationships between POC concentration and particle backscattering light [5][6][7], and it has been suggested that POC concentrations in oceanic surface waters can be estimated from ocean color remote sensing data [2,3,[5][6][7][8]. However, the spectral variability of the backscattering coefficients of suspended particles increases the difficulty in calculating POC from satellite data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations